A cross-sectional online survey on COVID19 related anxiety among students of Tertiary care center - Ganiger, Fakirappa B; Bijjal, Somashekhar; Gadad, Aran V; Mugali, Jitendra; Shaikh, Manal; Iti, Jannatbi (Nepal Journal of Neuroscience, 2022)
Background: COVID19 pandemic has deleterious effect on mental health of people around world. Like medical professionals, students of tertiary care center are also at higher risk of developing anxiety related to COVID19.Objectives: To assess severity of COVID19 related anxiety and identify underlying risk factors among students of different courses of tertiary care center.Materials and Methods: A cross-sectional online survey was conducted including 704 students aged above 18 years from different courses of tertiary care center. Study was conducted after obtaining clearance from Institutional Ethical Committee and informed consent was obtained online. Anxiety related to COVID19 was assessed using COVI19 Anxiety Syndrome Scale (COVID19ASS). Statistical analysis for descriptive data was done by using mean and percentage.Results: Study comprised of 50.4% female and 49.6% male students with mean age of 20+4 and 21+3 years respectively. Mean COVID19ASS scores of male and female students was found to be 18.6 (SD=4.3) and 19.7 (SD=3.8) with no statistically significant difference (p value=0.41, x2= 2.87, df- 3). In factor analysis, age group 18- 20 years, students in first year MBBS, first and second year of paramedical/nursing course, postgraduates, history of COVID19 infection in the past, history of either infection or death due to COVID19 in family or friend were significant risk factors for perseveration and avoidance behavior.Conclusion: Students who report of pandemic associated anxiety should be thoroughly interviewed for severity of symptoms. This may help in early identification of mal-adaptive behavior, so that early intervention either pharmacological or psychological therapy can be initiated.